Potential of chitosan oligosaccharide gel as a cavity cleanser against adhesive restoration adhesive on the cavity wall - Madya Theresa TARIGAN; Trimurni ABIDIN (Dentistry Faculty, 2022)
Cavity cleanser is a cavity cleaner with ideal properties such as being biocompatible, antibacterial,removing smear layers, and not interfering with the adhesive bond. This study aims to examine the potential of gelchitosan oligosaccharide (COS) as a cavity cleanser on the adhesion of the restoration to the cavity wall. Thirty-twomandibular premolars with class V restorations are divided into two groups with 2% COS gel and 2% chlorhexidinedigluconate (CHX). Samples were immersed in 2% methylene blue, cut longitudinally, observed under astereomicroscope with 1x magnification, and scored 0-3. The Mann-Whitney test was used to see the potential of gelCOS as a cavity cleanser. The results showed a significant difference between the two groups at the edge of theenamel junction restoration (p=0.038) and the dentin junction restoration (p=0.027). The mean microleakage score ingroup 1 showed better results at the enamel junction (1.19 1.328) and the dentin junction (2.001.211). It shows that2% COS gel has the potential as a cavity cleanser. There was a significant difference between the two groups as acavity cleanser on the adhesion of adhesive restorations to the cavity wall.KEYWORDS: cavity cleanser; chitosan oligosaccharide; chlorhexidine digluconate; microleakage